The Effect of Endoscopic Resection on Short-Term Surgical Outcomes in Patients with Additional Laparoscopic Gastrectomy after Non-Curative Resection for Gastric Cancer - Lee, Eun-Gyeong (J Gastric Cancer, 2017)
PURPOSE: Endoscopic submucosal dissection (ESD) in early gastric cancer causes an artificial gastric ulcer and local inflammation that has a negative intraprocedural impact on additional laparoscopic gastrectomy in patients with noncurative ESD. In this study, we analyzed the effect of ESD on short-term surgical outcomes and evaluated the risk factors. MATERIALS AND METHODS: From January 2003 to January 2013, 1,704 patients of the National Cancer Center underwent laparoscopic gastrectomy with lymph node dissection because of preoperative stage Ia or Ib gastric cancer. They were divided into 2 groups: (1) with preoperative ESD or (2) without preoperative ESD. Clinicopathologic factors and short-term surgical outcomes were retrospectively evaluated along with risk factors such as preoperative ESD. RESULTS: Several characteristics differed between patients who underwent ESD-surgery (n=199) or surgery alone (n=1,505). The mean interval from the ESD procedure to the operation was 43.03 days. Estimated blood loss, open conversion rate, mean operation time, and length of hospital stay were not different between the 2 groups. Postoperative complications occurred in 23 patients (11.56%) in the ESD-surgery group and in 189 patients (12.56%) in the surgery-only group, and 3 deaths occurred among patients with complications (1 patient [ESD-surgery group] vs. 2 patients [surgery-only group]; P=0.688). A history of ESD was not significantly associated with postoperative complications (P=0.688). Multivariate analysis showed that male sex (P=0.008) and laparoscopic total or proximal gastrectomy (P=0.000) were independently associated with postoperative complications. CONCLUSIONS: ESD did not affect short-term surgical outcomes during and after an additional laparoscopic gastrectomy.